Brand Equity Dimensions of Mediation in Satisfaction as Customer Loyalty - Anisatul Fauziah; Jesi Irwanto (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2020)
Brand equity Strong will deliver value, both for customers and the company. Brand equity can be reflected in the way consumers think, feel, and act in the relationship by brand, price, market share, and profitability of a given brand for the company. This study aimed to examine the effect of the dimensions of brand equity consisting of brand awareness, brand association and perception of significant-quality partially and simultaneously on customer satisfaction and customer loyalty. Examine the effect of satisfaction on loyalty and satisfaction as mediator test the influence of the dimensions of brand equity consisting of brand awareness, brand association and a significant perceived quality on customer loyalty superior products glorious in Lumajang banana chips. Respondents in this study were Lumajang community and consumers totalling 200 respondents. With Sobel path analysis and testing of the obtained results of the research test brand awareness, brand association and perceived quality simultaneously significant effect on satisfaction, brand awareness while partial no effect on satisfaction. Simultaneously and partially brand awareness, brand association and perceived quality have a significant effect on loyalty. Satisfaction significant effect on loyalty and satisfaction may be a mediator on the effect of brand awareness, brand association and perception of significant quality on loyalty. Limitations of this study only examined the consumer from Lumajang community, so expected this limitation bias was investigated in future studies.